2008
DOI: 10.1104/pp.108.124024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leaf-Level Spatial Variability in Photosynthetic Capacity on Biochemical Parameter Estimates Using the Farquhar Model: A Theoretical Analysis  

Abstract: Application of the widely used Farquhar model of photosynthesis in interpretation of gas exchange data assumes that photosynthetic properties are homogeneous throughout the leaf. Previous studies showed that heterogeneity in stomatal conductance (g s ) across a leaf could affect the shape of the measured leaf photosynthetic CO 2 uptake rate (A) versus intercellular CO 2 concentration (C i ) response curve and, in turn, estimation of the critical biochemical parameters of this model. These are the maximum rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 37 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…We attempted to isolate knock-out (KO) lines in each of these genes but were only able to isolate homozygous T-DNA insertions in ACBP3 (At4g24230), ACBP4 (At3g05420), and ACBP6 (At1g31812) genes. Similar lines were used in previous studies where the KO mutations were confirmed by functional complementation with the respective wt gene (Chen et al, 2008; Xiao et al, 2008, 2010). The KO mutations were verified by RT-PCR, which confirmed the absence of detectable transcripts in the respective lines (Figure A1 in Appendix).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We attempted to isolate knock-out (KO) lines in each of these genes but were only able to isolate homozygous T-DNA insertions in ACBP3 (At4g24230), ACBP4 (At3g05420), and ACBP6 (At1g31812) genes. Similar lines were used in previous studies where the KO mutations were confirmed by functional complementation with the respective wt gene (Chen et al, 2008; Xiao et al, 2008, 2010). The KO mutations were verified by RT-PCR, which confirmed the absence of detectable transcripts in the respective lines (Figure A1 in Appendix).…”
Section: Resultsmentioning
confidence: 92%
“…The genotypes were determined by PCR. The SALK lines used here have been used in several earlier studies (Chen et al, 2008; Xiao et al, 2008, 2010). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the LM image analysis will allow calculation of cellular and some organellar dimensions, as well as intracellular spaces along the leaf gradient that will be needed to calculate better diffusion rates in flux models of, for example, photosynthesis and cell-cell exchange of metabolites and inorganic molecules (e.g., CO 2 ) (Jenkins et al, 1989;Farquhar et al, 2001;Zhu et al, 2007;Chen et al, 2008), as well as functional-structural or three-dimensional virtual plant modeling (Vos et al, 2010). We functionally annotated >4300 identified maize proteins and assigned many to a subcellular localization (in particular, plastids, mitochondria, peroxisomes, and vacuoles) based on experimental data for maize proteins, in combination with information for their best homologs in Arabidopsis, sorghum (Sorghum bicolor), rice, and others.…”
Section: Resources For the Plant Communitymentioning
confidence: 99%
“…4, this ratio will deviate up to 24% over the leaf area. Chen et al (2008) showed that heterogeneity of photosynthetic parameters in leaves during gas-exchange measurements affects biochemical parameter estimates using the Farquhar model (Farquhar et al 1980). An increased heterogeneity of photosynthetic parameters due to a heterogeneous light distribution will make biochemical parameter estimates less reliable.…”
Section: Discussionmentioning
confidence: 99%